Состав песчаников в продуктивных горизонтах пермских битумных залежей Татарстана - Хасанов Ринат Радикович; Муллакаев Алмаз Ильясович; Дусманов Евгений Николаевич (Федеральное государственное автономное образовательное учреждение высшего образования «Казанский (Приволжский) федеральный университет», 2017)
В статье рассмотрены особенности песчаников продуктивных горизонтов пермских битуминозных отложений Татарстана. Состав и внутренняя структура песчаников изучены методами оптической микроскопии, электронного парамагнитного резонанса и электронной микроскопии с использованием физических и химических методов. Исследованные песчаники относятся к граувакковой группе. В составе обломочного материала песчаников встречаются зерна полевого шпата, кварца, слюды, а также частицы вулканических пород. Характер и состав цемента являются важными параметрами, определяющими фильтрационно-емкостные свойства осадочных пород. Битумные залежи характеризуются вертикальной зональностью, которая выражается в чередовании участков с различной степенью цементации пород.The features of sandstones in productive horizons of the Permian bituminous deposits of Tatarstan (Russia) have been considered. The composition and internal structure of sandstones have been studied by optical microscopy, electron paramagnetic resonance (EPR), and electron microscopy, as well as using a number of physical and chemical methods to solve special problems. The investigated sandstones belong to the greywacke group. The clastic material of sandstones contains grains of feldspar, quartz, mica, and particles of volcanic rocks. The nature and composition of cement are important parameters that determine the filtration-capacity properties of sedimentary rocks. Bituminous deposits are characterized by vertical zoning, which is expressed in the alternation of sites with varying degrees of cementation of rocks. Attention has been also paid to post-sedimentation processes, such as pyritization and calcification. Pyrite forms rare xenomorphic isometric grains. The formation of pyrite occurs in diagenesis and is associated with the processes of biogenic sulfate reduction. The source of calcium for the crystallization of dispersed calcite in the porous space of sandstones is the underground waters of red-colored Ufimian deposits characterized by the alkaline properties favorable for calcium migration. According to the data of X-ray computed tomography, the internal space of the studied rocks is not homogeneous and represented by a system of communicated and isolated pores. In the studied samples, two types of organic matter differing in organic radicals have been detected. The first type is an organic substance of coal origin. The second type of organic matter belongs to the oil origin and refers to bitumens in its properties. The presence of a significant percentage of asphaltenes in the bitumen composition indicates the destruction of the oil substance in the near-surface conditions.
Keywords: БИТУМЫ; Пермская; ПЕСКИ И ПЕСЧАНИКИ; МИНЕРАЛЬНЫЙ СОСТАВ; КОЛЛЕКТОРСКИЕ СВОЙСТВА; СТРУКТУРА; BITUMENS; SANDS AND SANDSTONES; MINERAL COMPOSITION; RESERVOIR PROPERTIES; STRUCTURE; 552.51; Палеозой::Пермская